What motivates people to purchase virtual items via gacha mechanics of video games? A case study of Chinese game players - Zeng, Ziyan (2018)
Game industry is booming nowadays. Regarding the rapid expansion of global games market, more companies have not only devoted themselves to entertain consumers, but have also kept on innovating the business models to adapt to the times. Thus, a variety of new monetization methods are created by combining the features of traditional monetization schemes. Gacha mechanism is the monetization method created via combining the idea of vending machine of capsule toys with traditional in-game purchase method. Though the introduction of it brings in a huge success in enhancing the profitability of video games in many countries, due to its feature of randomness that players cannot assess the in-game content before actually purchasing it through this type of mechanics, the adoption of gacha mechanism in video games stays in controversial just like gambling activities.